Decreased level of soluble receptor activator of nuclear factor-κβ ligand (sRANKL) in overweight and obese children - Erazmus, Michał; Rumińska, Małgorzata; Witkowska-Sędek, Ewelina; Kucharska, Anna M.; Stelmaszczyk-Emmel, Anna; Majcher, Anna; Pyrżak, Beata (Frontiers in Endocrinology, 2022)
Introduction: Childhood obesity contributes to the development of cardiovascular diseases. The molecular pathway – receptor activator of nuclear factor-κβ ligand (RANKL), its receptor RANK and osteoprotegerin (OPG) - takes part not only in bone metabolism but is also involved in the atherosclerosis process. RANKL stimulates osteogenic differentiation and calcification of vascular smooth cells. The associations between the OPG-sRANKL system and various cardiovascular risk factors were displayed. We aimed to evaluate the relationships between serum sRANKL (soluble RANKL) levels and the OPG/sRANKL ratio with cardiometabolic risk factors in overweight and obese children. Material and methods: The study included 70 children with overweight and obesity (mean age 13.0 ± 2.8) and 35 age-matched normal weight, healthy peers as a control group. In all patients, anthropometric measurements and laboratory tests were performed. Additionally, an oral glucose tolerance test (OGTT) was made only in overweight and obese children. Atherogenic and insulin resistance indices were calculated. Results: Overweight and obese children had lower sRANKL levels compared to the control group (median 276.95 vs 325.90, p=0.011), and consequently a higher OPG/sRANKL ratio (0.02 vs 0.01, p = 0.013). The studied children in the lowest quartile of sRANKL levels had higher body weight, Body Mass Index, waist circumference and increased glucose and insulin levels 60 minutes after OGTT and higher uric acid values compared to children in the highest quartile. In multivariable linear regression analysis sRANKL negatively correlated only with uric acid (β = - 0.508, p = 0.041). No association was found for the OPG/sRANKL ratio. Conclusion: Excess fat mass seems to alter the OPG/RANKL ratio mainly by reducing serum sRANKL levels. The correlation between sRANKL and uric acid may suggest a contribution of the OPG-sRANKL system in the cardiometabolic process, but that observation should be confirmed in future studies.